Essays on environmental shocks and economic development - McDermott, Thomas K. J. (Trinity College (Dublin, Ireland). Trinity Business School, 2013)
This thesis investigates the effects of environmental shocks, in the form of natural disasters and rainfall volatility, on economic development. I pursue both theoretical and empirical investigations of these issues. In Chapters 2 and 3, I present theoretical analyses of the impacts of disaster shocks on investment in physical and human capital, respectively. I show that the investment response to disasters depends on access to credit, and that where access to credit is problematic, investment will not fully compensate for the destruction of assets due to the disaster event. I also conduct empirical analysis of the effects of disasters for economic growth and for education and health outcomes, at a macro level, i.e. using country-level data. My analysis is based on a panel of data that covers 170 countries, for the period 1979-2007 and includes data on thousands of disaster events. I find, in contrast to some of the existing literature on the economics of natural disasters, that disasters can have persistent as opposed to transient impacts on economic growth. The persistence of the growth effects depends on the availability of credit in the affected region. The magnitude of the results is also economically meaningful; a disaster that occurs in a country with relatively weak financial sector development can completely wipe out economic growth for up to three years after the event, while the impact on growth rates will remain significant for up to 10 years.
Keywords: Business, Ph.D.; Ph.D. Trinity College Dublin